The Effect of Unripe Berlin Banana Flour on Superoxide Dismutase (SOD) in Dyslipidemic Rats - Damayati, Ratih Putri; Febriyatna, Ayu; Agustin, Firda (Media Gizi Indonesia, 2024)
Dyslipidemia is the occurrence of conditions that have abnormal lipid profile levels in the blood. Consumption of food sources of flavonoids and resistant starch is expected to play a role in dyslipidemia. Unripe Berlin banana flour (UBF) is source of flavonoids and resistant starches that benefit in dyslipidemia. This study aimed to determine the effect of giving UBF on SOD levels in dyslipidemic rats. This research used true experimental method with Pretest-Posttest and Control Group Design. This study used 30 rats divided into 5 groups K-, K +, P1 (UBF 0.144g /rat/day), P2 (UBF 0.288g /rat/ day), and P3 (UBF 0.576g/rat/day). The data were analyzed with one-way Anova and paired T-test. The results of the study showed that the values of SOD levels pre and post-intervention were not significantly different between groups. The mean of SOD levels pre-intervention showed that the K+, P1 and P3 groups were lower than K- group, then post-intervention at P1, P2 and P3 had higher SOD levels than K+ group. Meanwhile, the SOD levels of each group pre and post-UBF intervention in the P1 group were significantly different (p < 0.05), while in the P2 and P3 groups were not significantly different. This study concluded that giving raw Berlin banana flour at a dose of 0.144 g / day could increase the SOD levels in dyslipidemic rats.